Preparation of nanoemulsion using lipase-synthesized glucose monooleate through low energy technique / Muhammad Fakhrurazi Ahmad Fadzil - Muhammad Fakhrurazi , Ahmad Fadzil (2021)
In this study, glucose monooleate (GluO) was synthesized and compared to its counterpart i.e. Tween-80 (Tw-80) and Span-80 (Sp-80) to investigate the influence of the different hydrophilic head structure of the surfactants on emulsification property. Utilizing sugar molecules like glucose as the hydrophilic head group of surfactants is of interest as it has a high potential to be used as a targeted delivery agent. The main objective of this study is to investigate the capability of lipase synthesized GluO in the formation of O/W nanoemulsion in four different types of vegetable oils that are sunflower oil, olive oil, palm oil, and coconut oil through low energy method. Initial screening showed that GluO as a single surfactant was not able to produce nanoemulsion. However, incorporation of Cremophor EL (CrEL) helped in the formation of oil-in-water (O/W) nanoemulsion in sunflower and coconut oil at optimal CrEL: GluO and S:O ratios of 63:37 and 60:40 respectively. The formation of O/W emulsion using GluO-incorporated surfactant mixture was studied using optical polarizing microscopy (OPM), small angle X-ray scattering (SAXS), and Fourier-transform infrared spectroscopy (FTIR). Based on the results, it is hypothesized that the mechanism of nanoemulsion production using GluO-incorporated surfactant mixture involved the formation of a bi-continuous/lamellar phase structure at 40 % water content rather than the formation of multiple emulsion (O/W/O) before it was dispersed into nano-sized oil droplets with further addition of water.